A wide temperature range composite proton exchange membrane and preparation method thereof

By intercalating graphene oxide and poly(2,5-benzimidazole) composite materials with montmorillonite, nanopore structures and hydrogen bonds are constructed to fix phosphoric acid, which solves the problem of performance degradation of proton exchange membranes in a wide temperature domain, and achieves the realization of the performance of proton exchange membranes It has efficient proton conduction and water absorption and acid preservation capabilities, and broadens the temperature range of fuel cells.

CN115295846BActive Publication Date: 2024-12-27HUBEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211071877.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2024-12-27
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

The existing proton exchange membrane fuel cell technology is difficult to work efficiently in wide temperature ranges (room temperature to 200°C), especially in the low and high temperature conditions, which may cause degradation in performance or strict hydrothermal management.

Method used

Montmorillonite intercalated graphene oxide and poly(2,5-benzimidazole) composite materials are used to construct nanopore structures and hydrogen bonds to fix phosphoric acid, so as to achieve efficient conduction of the proton exchange membrane in a wide temperature domain.

Benefits of technology

It realizes efficient conduction of the proton exchange membrane under room temperature to high temperature conditions, broadens the temperature range of fuel cells, improves the water absorption and acid preservation ability and proton conductivity, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115295846B_ABST
    Figure CN115295846B_ABST
Patent Text Reader

Abstract

The invention discloses a wide temperature range composite proton exchange membrane and a preparation method thereof. The preparation method of the wide temperature range composite proton exchange membrane comprises the following steps: preparing a montmorillonite intercalated graphene oxide composite material; preparing a montmorillonite intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane. The present invention utilizes montmorillonite intercalated graphene oxide to prepare a nanomaterial with a pore structure, which has the ability to absorb water and fix phosphoric acid, and fills it with an ABPBI composite membrane, so that it can achieve efficient proton conduction under room temperature to high temperature conditions, thereby widening the use temperature range of proton exchange membrane fuel cells; the present invention greatly exerts the performance of the material itself, and its preparation process is simple and easy to operate, and the prepared composite membrane has good water absorption and acid retention capacity and high proton conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a wide-temperature-range composite proton exchange membrane and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) are one of the current research hotspots of new energy devices, and fuel cell vehicles are a hot research direction for many automobile manufacturers. As the core component of PEMFC, proton exchange membrane (PEM) directly determines the performance of PEMFC. According to the working temperature, it can be divided into low-temperature PEMFC (<100℃) and high-temperature PEMFC (100~200℃). At present, low-temperature PEMFC mainly uses Nafion membrane with a higher degree of commercialization, but this type of membrane material has strict requirements on temperature and humidity conditions, that is, the working temperature is <80℃ and the humidity is >80%RH, which means that the water and heat management of the entire fuel cell system is extremely strict during operation. In contrast, the high-temperature PEMFC using poly (2,5-) benzimidazole (ABPBI) doped with phosphoric acid (PA) not only has a high proton conductivity, but also can effectively solve the problems of water and heat management and raw material purity. However, this type of composite membrane is also limited by the working temperature, that is, it is easy to cause PA loss in a low temperature and water environment, which seriously reduces the performance of this type of membrane material. In addition, the loss of PA may also corrode the circuit and cause danger. Therefore, in the fuel cell vehicle industry, both high-temperature and low-temperature PEMFCs are subject to certain limitations, so it is very necessary to design a high-performance wide-temperature range PEMFC (i.e., operating temperature from room temperature to 200°C) that does not rely on water thermal management.

[0003] At present, there have been reports proposing the introduction of hydrophilic two-dimensional mineral materials and amphiphilic graphene to improve the water absorption and proton conductivity of proton exchange membranes. Chinese patent CN106977753B discloses a modified graphite oxide / montmorillonite / sulfonated polyvinyl alcohol composite proton exchange membrane and its preparation method and application. The composite membrane prepared by this patent has a high room temperature proton conductivity, but it is limited by the matrix membrane and cannot be used at high temperatures, and it is heavily dependent on the presence of water. Chinese patent CN114171764A discloses a proton exchange membrane and its preparation method. The modified proton exchange membrane prepared by this patent has a higher proton conductivity at 40-90°C, but it cannot be used at high temperatures. Chinese patent CN101414686A discloses a composite membrane and its application in high-temperature proton exchange membrane fuel cells. The operating temperature of the PEMFC prepared by this patent is 90-150°C, and it has the characteristic of not being able to be used at low temperatures.

[0004] In the above preparation methods, most of them are limited to low or high temperature use, and the wide temperature range of use characteristics are not achieved. Therefore, developing a simple and easy-to-use fuel cell that can be used under wide temperature conditions and has outstanding performance is an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a wide temperature range composite proton exchange membrane and a preparation method thereof, and solve the technical problem in the prior art that proton exchange membranes are limited to high or low temperature use.

[0006] A first aspect of the present invention provides a method for preparing a wide temperature range composite proton exchange membrane, comprising the following steps:

[0007] Preparation of montmorillonite intercalated graphene oxide composite materials;

[0008] Preparation of montmorillonite intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane.

[0009] The second aspect of the present invention provides a wide temperature range composite proton exchange membrane, which is obtained by the preparation method of the wide temperature range composite proton exchange membrane provided by the first aspect of the present invention.

[0010] Compared with the prior art, the beneficial effects of the present invention include:

[0011] (1) The present invention utilizes montmorillonite intercalated with graphene oxide to prepare a nanomaterial with a porous structure, which has the ability to absorb water and fix phosphoric acid, and fills the nanomaterial with the ABPBI composite membrane, so that it can achieve efficient proton conduction under room temperature to high temperature conditions, thereby broadening the operating temperature range of proton exchange membrane fuel cells;

[0012] (2) The present invention makes full use of the performance of the material itself, and its preparation process is simple and easy to operate. The prepared composite membrane has good water absorption and acid retention capacity and high proton conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is the water absorption test graph of different ABPBI composite membranes;

[0014] Figure 2 This is the PA loss rate test graph of different ABPBI composite membranes;

[0015] Figure 3 This is a test graph of the proton conductivity of different ABPBI composite membranes under 40-180℃ / 0%RH conditions;

[0016] Figure 4 This is a test graph of the proton conductivity of different ABPBI composite membranes under 40-90℃ / 98%RH conditions. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0018] A first aspect of the present invention provides a method for preparing a wide temperature range composite proton exchange membrane, comprising the following steps:

[0019] S1. preparing a montmorillonite intercalated graphene oxide composite material;

[0020] S2. Preparation of montmorillonite intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane.

[0021] In the present invention, the functions of graphene oxide and montmorillonite are as follows: a single layer or a few layers of GO is a two-dimensional wrinkled sheet nanomaterial with a huge specific surface area (2630m 2 / g) and many oxygen-containing hydrophilic functional groups, which can not only adsorb water molecules to achieve proton conduction at low temperatures, but also form hydrogen bonds between PA molecules to fix PA, which makes GO have the potential to be used in high-temperature PEMFC. Montmorillonite (MMT) is one of the representatives of two-dimensional clay minerals. Due to the isomorphic substitution phenomenon, it can adsorb hydronium ions and sodium and calcium ions between layers. On the one hand, this ion exchange performance can adsorb water to solve the problem of water shortage of proton exchange membranes under high temperature and low humidity conditions; on the other hand, it can fix PA in its unique pore structure to prevent PA loss, so it is expected to be used in wide temperature range PEMFC. When montmorillonite and graphene oxide, two two-dimensional materials, are blended with polymer materials separately, they are prone to agglomeration due to interfacial effects, resulting in poor proton exchange membrane effects. The present invention first prepares a two-dimensional layered stack by intercalating GO with MMT, which achieves co-exfoliation of the two materials while effectively preventing their agglomeration by destroying the interlayer van der Waals bonds; increasing the specific surface area can not only adsorb more free water, but the newly generated nanochannels can also be used for PA fixation, further realizing the wide temperature range of PEMFC.

[0022] In the present invention, in the above-mentioned montmorillonite intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range proton exchange membrane, the added amount of montmorillonite intercalated graphene oxide is 0.5%-1.5%, preferably 0.8%-1%, and more preferably 1%.

[0023] In the present invention, in the above-mentioned montmorillonite intercalated with graphene oxide, the mass ratio of montmorillonite to graphene oxide is 1:(0.8-1.2), preferably 1:1.

[0024] In the present invention, the steps of preparing the montmorillonite intercalated graphene oxide composite material include:

[0025] S11, dispersing montmorillonite (MMT) in deionized water, stirring at 90-100° C. for 6-8 hours, and then performing ultrasonic dispersion to obtain a montmorillonite dispersion; during this process, adding deionized water at intervals to keep the concentration of the dispersion stable; the concentration of the montmorillonite dispersion is 1-3 g / L, and further 2 g / L;

[0026] S12, dispersing graphene oxide (GO) in deionized water, stirring at 90-100° C. for 6-8 hours, and then performing ultrasonic dispersion to obtain a graphene oxide dispersion; during this process, adding deionized water at intervals to keep the concentration of the dispersion stable; the concentration of the graphene oxide dispersion is 1-3 g / L, and further 2 g / L;

[0027] S13, mixing the montmorillonite dispersion and the graphene oxide dispersion and stirring them evenly, and obtaining a montmorillonite intercalated graphene oxide composite material (GO-MMT) after drying; in this process, the stirring time is 12-36h.

[0028] In the present invention, the steps of preparing the montmorillonite intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane include:

[0029] S21, mixing 3,4-diaminobenzoic acid (DABA), montmorillonite intercalated graphene oxide composite material (GO-MMT), and part of methanesulfonic acid (MSA), and uniformly dispersing by ultrasonication to obtain a first mixture; in this process, the mass ratio of 3,4-diaminobenzoic acid to montmorillonite intercalated graphene oxide composite material (GO-MMT) is (80-300): 1;

[0030] S22, mixing the first mixture and phosphorus pentoxide (P2O5), and adding the remaining methane sulfonic acid (MSA) step by step, and continuing to disperse evenly by ultrasonic after the addition is completed to obtain a second mixture; in this process, the mass ratio of 3,4-diaminobenzoic acid to phosphorus pentoxide is 1: (1-3), preferably 1: 2; the remaining methane sulfonic acid is added in 4-5 steps;

[0031] S23, preheating the second mixture at 70-90°C for 0.5-1.5h, heating to 150-170°C, and prepolymerizing for 1-3h; then heating to 210-230°C, and condensing for 4-6h to obtain a viscous brown slurry; the process is carried out under nitrogen and stirring; during the prepolymerization, the rotation speed is 250-300rpm; during the condensation reaction, the rotation speed is 350-400rpm;

[0032] S24. Slowly pour the slurry into deionized water to make it into fibrous filaments, boil and wash it in alkaline solution and deionized water in turn, finally wash it with deionized water until it is neutral, and dry it to obtain a montmorillonite interlayered graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane.

[0033] Furthermore, the dosage ratio of 3,4-diaminobenzoic acid to methanesulfonic acid is (0.12-0.18) g: 1 ml. A dosage ratio that is too high will cause the molecular chain length to be too low during polymerization, affecting the mechanical strength of the composite membrane; a dosage ratio that is too low will increase the workload of subsequent washing to remove MSA, causing waste, preferably 0.15 g: 1 ml. Furthermore, the portion of methanesulfonic acid used in step S21 accounts for 40-60% of the total volume of methanesulfonic acid, preferably 50%.

[0034] The second aspect of the present invention provides a wide temperature range composite proton exchange membrane, which is obtained by the preparation method of the wide temperature range composite proton exchange membrane provided by the first aspect of the present invention.

[0035] Example 1

[0036] (1) Preparation of montmorillonite intercalated graphene oxide composite material: 0.2g MMT was dissolved in 100ml deionized water and magnetically stirred at 100℃ boiling water for 6h, where deionized water was added every 2h to maintain the solution at 100ml, and then the dissolved MMT suspension was ultrasonically treated for 1h to fully disperse; at the same time, 0.2g GO was pretreated in the same way and under the same conditions. Subsequently, the GO suspension was poured into the MMT suspension, and the mixture was magnetically stirred at 80℃ for 24h, and finally dried in an oven at 60℃ to obtain a GO intercalated MMT layered composite, which was recorded as GO-MMT.

[0037] (2) ABPBI composite membrane with an inorganic addition amount of 0.5% was prepared by in-situ synthesis and casting method: 3.0g 3,4-diaminobenzoic acid (DABA) and 0.01145g GO-MMT layered stack were added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and continuously ultrasonicated; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added at 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonication was continued for 1h to fully disperse it. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15 minutes to ensure N2 atmosphere; after preheating at 80°C for 1 hour, the device was heated to 160°C, the speed was set to 250-300 rpm, and prepolymerization was performed for 2 hours; then the temperature was raised to 220°C, the speed was increased to 350-400 rpm, and a viscous brown slurry was obtained after condensation reaction for 5 hours. The obtained slurry was slowly poured into deionized water to make it into a fibrous filament, and then boiled and washed in NaOH alkali solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain 0.5% GO-MMT / ABPBI, which was used for subsequent tests.

[0038] Example 2

[0039] (1) The steps for preparing the montmorillonite intercalated graphene oxide composite material are the same as those in Example 1.

[0040] (2) ABPBI composite membrane with an inorganic addition amount of 0.8% was prepared by in-situ synthesis and casting method: 3.0g 3,4-diaminobenzoic acid (DABA) and 0.01832g GO-MMT layered stack were added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and continuously ultrasonicated; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added at 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonication was continued for 1h to fully disperse it. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15 minutes to ensure N2 atmosphere; after preheating at 80°C for 1 hour, the device was heated to 160°C, the speed was set to 250-300 rpm, and prepolymerization was performed for 2 hours; then the temperature was raised to 220°C, the speed was increased to 350-400 rpm, and a viscous brown slurry was obtained after condensation reaction for 5 hours. The obtained slurry was slowly poured into deionized water to make it into fiber filaments, and then boiled and washed in NaOH alkali solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain 0.8% GO-MMT / ABPBI, which was used for subsequent tests.

[0041] Example 3

[0042] (1) The steps for preparing the montmorillonite intercalated graphene oxide composite material are the same as those in Example 1.

[0043] (2) ABPBI composite membrane with an inorganic addition amount of 1.0% was prepared by in-situ synthesis and casting method: 3.0g 3,4-diaminobenzoic acid (DABA) and 0.02290g GO-MMT layered stack were added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and continuously ultrasonicated; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonication was continued for 1h to fully disperse it. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15 minutes to ensure N2 atmosphere; after preheating at 80°C for 1 hour, the device was heated to 160°C, the speed was set to 250-300 rpm, and prepolymerization was performed for 2 hours; then the temperature was raised to 220°C, the speed was increased to 350-400 rpm, and a viscous brown slurry was obtained after condensation reaction for 5 hours. The obtained slurry was slowly poured into deionized water to make it into a fibrous filament, and then boiled and washed in NaOH alkali solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain 1.0% GO-MMT / ABPBI, which was used for subsequent tests.

[0044] Example 4

[0045] (1) The steps for preparing the montmorillonite intercalated graphene oxide composite material are the same as those in Example 1.

[0046] (2) ABPBI composite membrane with an inorganic addition of 1.2% was prepared by in-situ synthesis and casting: 3.0g 3,4-diaminobenzoic acid (DABA) and 0.02748g GO-MMT layered stack were added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and continuously ultrasonicated; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonication was continued for 1h to fully disperse it. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15 minutes to ensure N2 atmosphere; after preheating at 80°C for 1 hour, the device was heated to 160°C, the speed was set to 250-300 rpm, and prepolymerization was performed for 2 hours; then the temperature was raised to 220°C, the speed was increased to 350-400 rpm, and a viscous brown slurry was obtained after condensation reaction for 5 hours. The obtained slurry was slowly poured into deionized water to make it into fiber filaments, and then boiled and washed in NaOH alkali solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain 1.2% GO-MMT / ABPBI, which was used for subsequent tests.

[0047] Example 5

[0048] (1) The steps for preparing the montmorillonite intercalated graphene oxide composite material are the same as those in Example 1.

[0049] (2) ABPBI composite membrane with an inorganic addition of 1.5% was prepared by in-situ synthesis and casting: 3.0g 3,4-diaminobenzoic acid (DABA) and 0.03435g GO-MMT layered stack were added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and continuously ultrasonicated; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonication was continued for 1h to fully disperse it. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15 minutes to ensure N2 atmosphere; after preheating at 80°C for 1 hour, the device was heated to 160°C, the speed was set to 250-300 rpm, and prepolymerization was performed for 2 hours; then the temperature was raised to 220°C, the speed was increased to 350-400 rpm, and a viscous brown slurry was obtained after condensation reaction for 5 hours. The obtained slurry was slowly poured into deionized water to make it into fiber filaments, and then boiled and washed in NaOH alkali solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain 1.5% GO-MMT / ABPBI, which was used for subsequent tests.

[0050] Comparative Example 1

[0051] Pure ABPBI composite membrane was prepared by in-situ synthesis and casting method: 3.0g 3,4-diaminobenzoic acid (DABA) was added to a three-necked flask containing 10ml methanesulfonic acid (MSA) and ultrasonic treatment was continued; 6g phosphorus pentoxide (P2O5) was added after 1h, and then 10ml MSA was added 2ml every 20min, and the addition was completed in 5 times; when all MSA was added, ultrasonic treatment was continued for 1h to fully disperse. Then a sand bath was used to build a reaction device. Before starting the synthesis reaction, N2 was first introduced for 15min to ensure N2 atmosphere; after preheating at 80℃ for 1h, the device was heated to 160℃, the speed was set to 250-300rpm, and prepolymerization was carried out for 2h; then the temperature was raised to 220℃, the speed was increased to 350-400rpm, and a viscous brown slurry was obtained after condensation reaction for 5h. The prepared slurry was slowly poured into deionized water to make it into fibrous filaments, and then boiled and washed in NaOH solution and deionized water for 6 hours each, and finally washed with deionized water until neutral, and placed in a vacuum drying oven for 24 hours to obtain ABPBI, which was used for subsequent tests.

[0052] Experimental Group

[0053] (1) Analysis of water absorption performance of ABPBI composite membrane

[0054] First, the ABPBI composite membrane was 2 Cut the sample with a knife, set the vacuum drying oven temperature to 120℃ and dry it for 24h, then weigh the weight of the dried composite film as W. dry Then soak the proton exchange membrane in deionized water for 24 hours, wipe the water on the membrane surface with dust-free paper, and weigh its wet weight W wet The water absorption rate of ABPBI composite membrane can be calculated by the following formula:

[0055]

[0056] W wet —Wet weight of proton exchange composite membrane;

[0057] W dry —Dry weight of proton exchange composite membrane.

[0058] (2) PA loss rate test

[0059] Cut the ABPBI composite membrane into 1×1cm 2 The size of the membrane was placed in a vacuum drying oven for 24 hours and then immersed in a 70% PA solution for 72 hours. In order to remove the free PA and residual MSA in the membrane, a certain mass fraction of NaOH solution was prepared to wash the ABPBI composite membrane, and then it was repeatedly washed with deionized water. After that, the surface moisture was wiped off with dust-free paper and its weight was weighed. aThen, the film was dried in a vacuum oven at 110°C for 24 hours to remove the water in the film and its weight was measured. b Then put it into deionized water and boil it. Within the first hour, take out the membrane at 20 minutes, 40 minutes, and 60 minutes. Wipe the surface moisture with dust-free paper and weigh it, which are recorded as W1, W2, and W3 respectively. In the next 4 hours, weigh it every 1 hour, which are recorded as W4, W5, W6, and W7 respectively. PA loss rate of membrane material (W r ) is calculated by the following formula:

[0060]

[0061] (3) Proton conductivity test of ABPBI composite membrane

[0062] The proton conductivity of the ABPBI composite membrane was tested by the electrochemical workstation in conjunction with a constant temperature and humidity test chamber according to the AC impedance method. The model of the electrochemical workstation is PARSTAT 4000, and the model of the constant temperature and humidity test chamber is PL-80. The test was carried out by the double electrode method, and there are two test conditions: one is a wide temperature range of 40-180°C and a humidity of 0% RH; the other is a temperature range of 40-90°C and a humidity of 98% RH. The proton conductivity (σ) of the ABPBI composite membrane is calculated by the following formula:

[0063]

[0064] d—composite film thickness;

[0065] R—impedance of membrane (Ω);

[0066] A—Contact area between the measured membrane and the electrode.

[0067] See also Figure 1 , the basic imidazole structure in the pure ABPBI molecular chain can combine with water molecules through hydrogen bonds, and its saturated water absorption rate is 24.64%. In contrast, the water absorption rates of 0.5% GO-MMT / ABPBI, 0.8% GO-MMT / ABPBI, 1.0% GO-MMT / ABPBI, 1.2% GO-MMT / ABPBI, and 1.5% GO-MMT / ABPBI composite membranes can reach 30.75%, 32.70%, 34.12%, 33.25%, and 31.51%, respectively, which are all better than the water absorption rate of pure ABPBI membranes. The excellent water absorption performance of these composite membranes is attributed to the fact that in addition to the basic imidazole groups in the main chain of the polymer matrix that can adsorb water, the added GO-MMT two-dimensional layered material has a large internal specific surface area that can adsorb water through ion exchange properties, and the large number of Si-OH groups on its surface can also fix water molecules, so that the GO-MMT / ABPBI composite membrane exhibits good water absorption. In addition, through Figure 1It can be seen that 1.0% GO-MMT / ABPBI has the highest water absorption.

[0068] See also Figure 2 , Figure 2 The PA loss of ABPBI membrane materials with similar PA doping levels under extreme conditions (i.e., boiling various ABPBI membranes in deionized water) was simulated. All PA-doped ABPBI membranes showed two stages of PA loss: the first stage was the initial 20 minutes, during which the free PA was quickly released in boiling water; the second stage was the period after that, which was characterized by the slow release of bound PA. With the addition of GO-MMT layered stacks, the PA loss was significantly reduced and equilibrium was reached quickly. Analysis of the reasons suggests that the GO-MMT stack has a special layered structure, in which a large number of PA molecules can be adsorbed in its layer space, and can be fixed by hydrogen bonds with the hydroxyl groups on the inner surface of MMT and the oxygen-containing functional groups on the surface of GO between layers. The PA molecules adsorbed on the surface are also adsorbed on Si-OH through hydrogen bonds. Therefore, under extreme conditions, the loss of PA molecules is reduced, and the acid absorption and solidification capacity of the composite membrane is enhanced. It can be seen that the GO-MMT / ABPBI composite membrane has both a high PA doping level and a low PA loss rate. Moreover, through Figure 2 It can be seen that 1.0% GO-MMT / ABPBI has the lowest PA loss.

[0069] See also Figure 3 , Figure 3 The proton conductivity test graph of ABPBI composite membrane under 40-180℃ / 0%RH conditions. The proton conductivity of GO-MMT / ABPBI composite membranes with similar PA doping levels is significantly higher than that of pure ABPBI membranes. In addition, the proton conductivity of 1.0% GO-MMT / ABPBI composite membrane under 180℃ and 0%RH conditions reaches 0.052S·cm -1 , which is lower than the proton conductivity of pure ABPBI membrane under the same conditions (0.030S·cm -1 ) is 66.7% higher.

[0070] See also Figure 4 , Figure 4 The proton conductivity test graph of ABPBI composite membrane under 40-90℃ / 98%RH conditions. The proton conductivity of GO-MMT / ABPBI composite membranes with similar PA doping levels is significantly higher than that of pure ABPBI membranes. The proton conductivity of 1.0% GO-MMT / ABPBI composite membrane under 90℃ and 98%RH conditions reaches 0.038S·cm -1 , which is lower than the proton conductivity of pure ABPBI membrane under the same conditions (0.022S·cm -1 ) is 72.2% higher.

[0071] In summary, the present invention introduces a hydrophilic two-dimensional mineral material montmorillonite and an amphiphilic graphene composite to prepare a layered stacking material with a slit-type pore structure. It not only fixes PA by constructing nanochannels, but also conducts protons at low temperatures by combining water molecules, thereby achieving a wide temperature range for PEMFC.

[0072] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a wide temperature range composite proton exchange membrane, characterized in that: The following steps are involved: Preparation of montmorillonite intercalated graphene oxide composites: montmorillonite was dispersed in deionized water and heated at 90-100 o C for 6-8 h, followed by ultrasonic dispersion to obtain a montmorillonite dispersion; graphene oxide was dispersed in deionized water and heated at 90-100 o C for 6-8 h, followed by ultrasonic dispersion to obtain a graphene oxide dispersion; the montmorillonite dispersion and the graphene oxide dispersion are mixed and stirred evenly, and dried to obtain a montmorillonite intercalated graphene oxide composite material; Preparation of montmorillonite inter-intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane: 3,4-diaminobenzoic acid, montmorillonite inter-intercalated graphene oxide composite material, and part of methane sulfonic acid are mixed and ultrasonically dispersed to obtain a first mixture; the first mixture and phosphorus pentoxide are mixed, and the remaining methane sulfonic acid is added step by step, and after the addition is completed, ultrasonically dispersed to obtain a second mixture; the second mixture is heated at 70-90°C. o Preheat at 0.5-1.5h, and heat to 150-170 o C, prepolymerize for 1-3 h; then heat to 210-230 o C, condensation reaction for 4-6 hours to obtain a viscous brown slurry; the slurry is slowly poured into deionized water to make it into fibrous filaments, and then boiled and washed in alkaline solution and deionized water, and finally washed with deionized water until neutral, and dried to obtain a montmorillonite interlayered graphene oxide / poly (2,5-benzimidazole) wide temperature range composite proton exchange membrane.

2. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: The mass ratio of the 3,4-diaminobenzoic acid to phosphorus pentoxide is 1:(1-3).

3. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: The dosage ratio of the 3,4-diaminobenzoic acid to methanesulfonic acid is (0.12-0.18) g: 1 ml; the partial methanesulfonic acid accounts for 40-60% of the total volume of methanesulfonic acid.

4. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: The preheating, prepolymerization and condensation reactions are all carried out under nitrogen and stirring conditions.

5. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: In the montmorillonite inter-intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range proton exchange membrane, the added amount of montmorillonite inter-intercalated graphene oxide is 0.5%-1.5%.

6. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: In the montmorillonite inter-intercalated graphene oxide / poly (2,5-benzimidazole) wide temperature range proton exchange membrane, the added amount of montmorillonite inter-intercalated graphene oxide is 0.8%-1%.

7. The method for preparing a wide temperature range composite proton exchange membrane according to claim 1, characterized in that: In the montmorillonite intercalated graphene oxide, the mass ratio of montmorillonite to graphene oxide is 1:(0.8-1.2).

8. A wide temperature range composite proton exchange membrane, characterized in that: The wide temperature range composite proton exchange membrane is obtained by the preparation method of the wide temperature range composite proton exchange membrane according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Compound film and application thereof for high-temperature fuel battery with proton exchange film

    CN101414686A

  • A high-strength solid electrolyte biomimetic ultrathin film and its preparation method

    CN106977753B

  • Proton exchange membrane and preparation method thereof

    CN114171764A

  • Hybrid membranes, method for production of hybrid membranes and fuel cells using such hybrid membranes

    US20090075141A1